WORKLOAD AND BURNOUT AMONG HEALTHCARE WORKERS: THE ROLE OF WORK-FAMILY CONFLICT AS A MEDIATOR AND HUMAN RESOURCE MANAGEMENT RESOURCES AS BUFFERS: A SYSTEMATIC REVIEW - Jurianto Gambir; Nur Afifah; Mustaruddin; Titik Rosnani (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
This systematic review examines the relationship between workload and burnout among healthcare workers, with work-family conflict (WFC) as a mediating mechanism and HRM resources as buffering factors. Following PRISMA guidelines, English-language studies published between 2015 and 2026 were screened, and 23 articles met the inclusion criteria. Of these, 21 reported a positive association between high workload and burnout, especially emotional exhaustion. Among 16 studies assessing WFC, 14 identified it as a mediator. Additionally, 18 studies found that organizational support, supportive leadership, family-friendly policies, adequate staffing, and positive work climates reduced burnout. Burnout thus reflects interacting work demands, family conflict, and organizational resources